HEMOLYSATE-MEDIATED PLATELET AGGREGATION: AN ADDITIONAL RISK MECHANISM CONTRIBUTING TO THROMBOSIS OF CONTINUOUS FLOW VENTRICULAR ASSIST DEVICES - Tran, Phat L. (Perfusion, 2015)
Despite the clinical success and growth in the utilization of continuous flow ventricular assist devices (cfVADs) for the treatment of advanced heart failure, hemolysis and thrombosis remain major limitations. Inadequate and/or ineffective anticoagulation regimens, combined with high pump speed and non-physiological flow patterns can result in hemolysis which often is accompanied by pump thrombosis. An unexpected increased in cfVADs thrombosis was reported by multiple major VAD implanting centers in 2014, highlighting the association of hemolysis, and a rise in lactate dehydrogenase (LDH) presaging thrombotic events. It is well established that thrombotic complications arise from abnormal shear stresses generated by cfVADs. What remains unknown is the link between cfVAD-associated hemolysis and pump thrombosis. Can hemolysis of red blood cells (RBCs) contribute to platelet aggregation thereby facilitating prothrombotic complication in cfVADs? Herein, we examine the effect of RBC-hemolysate and selected major constituents, i.e. LDH and plasma free hemoglobin (pHb) on platelet aggregation utilizing electrical resistance aggregometry. Our hypothesis is that elements of RBCs, released as a result of shear-mediated hemolysis, will contribute to platelet aggregation. We show that RBC-hemolysate and pHb, but not LDH, are direct contributors to platelet aggregation, posing an additional risk mechanism for cfVAD thrombosis.